Analisis Risiko dan Mitigasi pada Rantai Pasok di CV. Kopi Biji Palembang Menggunakan Metode Failure Mode And Effect Analysis (FMEA) - Putri, Melani; Anwar, Andreas (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze risks and develop mitigation strategies in the supply chain of CV Kopi Biji Palembang using the Failure Mode and Effect Analysis (FMEA) method. The research was conducted through direct observation, interviews, and data analysis covering procurement, production, storage, and distribution processes. Each identified risk was evaluated based on Severity, Occurrence, and Detection, then calculated into the Risk Priority Number (RPN). The results showed that the highest risks were related to delays in raw material supply and errors in the production process. Mitigation strategies were formulated to reduce the impact of these risks and improve operational efficiency. This research is expected to provide practical contributions for medium-scale coffee businesses in systematically managing supply chain risks.